Simplified stress analysis of hybrid (bolted/bonded) joints. (September 2017) - Paroissien, E.; Lachaud, F.; Schwartz, S.; Da Veiga, A.; Barrière, P.
Abstract: The load transfer in hybrid (bolted/bonded) – denoted HBB – single-lap joints is complicated due to the association of two different transfer modes (discrete and continuous) through elements with different stiffnesses. The Finite Element (FE) method can be used to address the stress analysis of those joints. However, analyses based on FE models are computationally expensive and it would be profitable to use simplified approaches enabling extensive parametric studies. Two among the authors of this paper participated in the development of a dedicated 1D-beam approach [25]. This paper presents an extension of this framework enabling (i) the analysis of HBB joints made of dissimilar laminated or monolithic adherends, and (ii) the introduction of non linear material behaviour for both the adhesive layer and the fasteners. The output data are the distributions of displacements and forces in the adherends and fasteners, as well as those of adhesive shear and peeling stresses, allowing for a fast assessment of the material behaviour and strength prediction of HBB joints. The use of this model is illustrated in the identification of the failure mechanisms of HBB joints under quasistatic loadings, based on experimental and numerical tests on single-lap HBB joint. It is worth mentioning that the model can support pure bonded and pure bolted configurations. It can be used during the presizing phase at the design office (possibly independently on commercial software), to obtain quickly mechanical performances and to help in decision making. Moreover, it was shown that the judicious choice of the adhesive material allows for a significant increase of the static and fatigue strength compared to pure bolted or bonded corresponding configurations [17, 24]. The model can then be used to formulate at best adhesive materials to optimize the mechanical performance of HBB joints according to work specifications.